Assessment and validation of the pet-owner relationship scale for Brazil - Lopes, Luis Felipe Dias; Lopes, Eduarda Grando; Lima, Mauren Pimentel; Lopes, Fillipe Grando; Pegoraro, Daniela; Saragozo, Rosangela de Arruda; Lauz, Thais Ribeiro; dos Santos, Joana Vieira (Frontiers in Psychology, 2024)
Introduction This study aimed to perform a cross-cultural adaptation of the cat-owner/dog-owner relationship scales. The method involved several stages: conceptual, item, semantic, operational, measurement, and functional equivalence. Procedures included translation, synthesis of translations, back-translation, consensus on the English versions, external evaluation by the original authors, expert committee evaluation, and pre-tests. Methods The study surveyed 234 pet owners across Brazil using a 20-item questionnaire. Data analysis utilized confirmatory factor analysis, covariance-based modeling, and multigroup analysis. Results The study confirmed the content and construct validity of the model, demonstrating good convergent validity. Hypotheses testing revealed significant inverse relationships between Perceived Cost and Perceived Emotional Closeness, and between Perceived Cost and Pet-Owner Interactions. A positive correlation was found between Perceived Emotional Closeness and Pet-Owner Interactions, with Perceived Emotional Closeness also mediating the relationship between Perceived Cost and Pet-Owner Interactions. No significant differences were found across different pet owner groups, indicating the scale’s invariance and reliability across various demographics. Discussion The study significantly expands understanding of the complex dynamics in pet-owner relationships and emphasizes the interplay between emotional and practical factors. It offers valuable insights for future research and practices in animal and human welfare.